Evaluation of multimedia collections and services of the National Reference Library, Multimedia Centre. - Tan, Song Young. (2008)
This study looked into the existing multimedia collections and services at the Multimedia Centre and their usage by users. It also examined the users awareness about the Centre, services provided, their impression of the multimedia collections, and the facilities and organizational layout.